Distributed medium access control protocol based on successive collision detection for dense wireless sensor networks. (August 2016) - Choi, Hyun-Ho; Lee, Howon; Kim, Sanghoon; Lee, Jung-Ryun; Lee, In-Ho
The medium access control protocol plays an important role to decrease access collisions in dense wireless sensor networks where multiple sensors in the same vicinity attempt to transmit a packet simultaneously. In this article, we propose a distributed medium access control protocol that uses successive multiple collision detection phases for dense wireless sensor network environments by enhancing the typical carrier sense multiple access with collision resolution protocol that uses only a single collision detection phase. In the proposed medium access control protocol, colliding stations are filtered in each collision detection phase and only surviving stations compete again in the next collision detection phase. Therefore, the collision detection probability becomes higher as the collision detection phases proceed. Utilizing the successive multiple collision detection phases, we analyze the throughput numerically and find optimal operating parameters—such as the number of collision detection phases and the number of collision detection slots per phase—that maximize the throughput. Analysis and simulation results show that the proposed medium access control protocol using the successive collision detection technique significantly outperforms the conventional carrier sense multiple access with collision resolution protocol.